Inhibition of Bruton's Tyrosine Kinase Protects Against Burn Sepsis-Induced Intestinal Injury - Wan, Jia; Yu, Xi; Niu, Jia-Qi; Qiu, Le; Wang, Fei; Chen, Xu-Lin (Frontiers in Medicine, 2022)
This study aimed to investigate the role and molecular mechanisms of Bruton's tyrosine kinase (BTK), a member of the Tec family in burn sepsis-induced intestinal injury. Eighty C57BL/6 mice were randomly divided into four groups: the sham group, the burn group, the burn + sepsis group, and the burn + sepsis + LFM-A13 (a selective BTK inhibitor) group. The dynamic expression profiles of BTK and p-BTK in the intestine were measured by Western blot analysis. Intestinal histopathological changes and cellular apoptosis were determined. Inflammatory cytokines in serum and intestinal tissue were examined through enzyme-linked immunosorbent assay. Myeloperoxidase (MPO) activity was determined via a colorimetric assay. Intestinal p-BTK expression in the burn+sepsis group was significantly increased compared with that in the sham and burn groups. In the burn + sepsis group, the p-BTK expression level increased over time, peaked at 12, and then decreased at 24 h. LFM-A13 administration significantly inhibited p-BTK expression in the intestine. In contrast to the sham and burn groups, the burn + sepsis group exhibited obvious histopathological changes, which gradually aggravated over time. LFM-A13 also reduced the histopathological changes and cellular apoptosis in intestinal tissues, inhibited the inflammatory cytokines IL-4, IL-6, and TNF-α in serum and intestinal tissues, and significantly inhibited the increase in intestinal MPO activity induced by burn sepsis. BTK activation is one important aspect of the signaling event that may mediate the release of the anti-inflammatory cytokine IL-4 and the pro-inflammatory cytokines IL-6 and TNF-α; oxidative stress; and intestinal cell apoptosis. Thus, it contributes to burn sepsis-induced intestinal injury.